Factors associated with medication interruption among outpatients with severe mental illness exposed to COVID-19 - Jiao, Jian; Ji, Yuanyi; Ren, Hua; Hao, Yanni; Shen, Xiaoling; Dong, Zaiquan (Frontiers in Public Health, 2023)
Many patients with severe mental illness (SMI) relapsed and deteriorated during the COVID-19 pandemic, as they experienced medication interruption. This study aimed to investigate factors affecting medication interruption in patients with SMI during the COVID-19 pandemic. A total of 2,077 patients with SMI participated in an online survey on medication interruption during the COVID-19 outbreak. The questionnaire comprised six parts: basic demographic information, COVID-19 exposure, state of disease, medication compliance before COVID-19, medication interruption during COVID-19, and the specific impact and needs. A total of 2,017 valid questionnaires were collected. Nearly 50% of patients with SMI have been affected to varying degrees of life expectancy and treatment. Among them, 74 patients stopped taking medicines for more than 14 days without a prescription. Logistic regression analysis showed that cohabitant exposure [OR=26.629; 95% CI (3.293-215.323), p = 0.002], medication partial compliance and non-compliance pre-COVID-19 [OR=11.109; 95% CI (6.093-20.251), p < 0.001; OR=20.115; 95% CI (10.490-38.571), p < 0.001], and disease status [OR = 0.326; 95% CI (0.188-0.564), p < 0.001] were related to medication interruption. More than 50% of the patients wanted help in taking medications, follow-up, and receiving more financial support and protective materials. We found that the daily lives of patients with SMI were much more susceptible to impact during the pandemic. Patients with a history of partial or non-medication compliance before COVID-19 and an unstable disease state are more easily affected by pandemics and epidemics and need extra attention should similar large-scale outbreaks occur in the future.